PENGARUH MODEL RECIPROCAL TEACHING BERBANTUAN MASALAH AUTENTIK TERHADAP KEMAMPUAN PEMECAHAN MASALAH DAN KONEKSI MATEMATIS SISWA - Ni Made Erlinta Devi; I Wayan Puja Astawa; Sariyasa Sariyasa (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2021)
Abstract This study aimed to compare problem solving ability and mathematical connection of students who were learned using reciprocal teaching model with authentic problems and students who were learned using conventional learning. This research applied quasi experiment method with control only group design. The sample of this study consisted of 75 junior high school students who are divided into two groups. The experimental group was learned using reciprocal teaching model with authentic problems and the control group received conventional learning. The data was collected using test and analized using Manova. The result showed that problem solving abilities and mathematical connection of students who were learned using reciprocal teaching model with authentic problems were higher than students who were learned by conventional learning (F = 4.310, p(0,014). Thus, it can be concluded that the reciprocal teaching model with authentic problem has positive effect on problem solving abilities and mathematical connection of students.